The legal nature of the payment of an arbitration agreement - Nabil, Wnughy; Shazly, Zibar Al- (Journal of Legal and Political Studies, 2021)
Arbitration in investment disputes may raise many defenses, and the purpose of determining defenses in the Code of Civil Procedures to clarify what is related to the subject of the dispute and the latter are called substantive defences, and this may be invoked in any case in which the case, These actions may not be initiate dafter the speech on the subject, including with regard to the acceptance of the case or the conditions of the right of action.
Keywords: Arbitration; investment; Code of Civil Procedures; substantive defences; right of action